Capacity of Cone-Shaped Hollow Flexible Reinforced Concrete Foundation (CHFRF) in Sand under Horizontal Loading - Shanshan Li; Yukun Zhang; Dayong Li (Advances in Materials Science and Engineering)
The cone-shaped hollow flexible reinforced concrete foundation (CHFRF) is an innovative type of mountain wind turbine foundation, which outperforms the regular mountain wind turbine foundation in reducing the steel and concrete and protecting the surrounding vegetation for the cavity absorbs soil obtained from excavating the foundation pit. Moreover, the rubber layer installed between the wall of CHFRF and the surrounding ground increases foundation flexibility and releases the larger overturning moment induced by wind. The rubber layer is made of alternately laminated rubber and steel. The objectives of this research are to study the lateral bearing behaviors of the CHFRF under monotonic and cyclic lateral loading in sand by model tests and FEM simulations. The results reveal that the CHFRF rotates during loading; and, in the ultimate state, the rotation center is located at a depth of approximately 0.6–0.65 times the foundation height and is 0.15–0.18 times the diameter of the foundation away from its centerline as well. The lateral bearing capacity of the CHFRF improves with the increase of embedded depth and vertical load applied to the foundation. Moreover, compared to the CHFRF without the rubber layer, the rubber layer can reduce the earth pressure along the wall of CHFRF by 22% and decrease the deformed range of the soil surrounding the foundation, revealing that it can reduce the loads transferred to the surrounding soil for extending the service life of the foundation. However, the thickness and stiffness of the rubber layer are important factors influencing the lateral bearing capacity and the energy dissipation of the foundation. Moreover, it should be noted that the energy dissipation mainly comes from the steel of the rubber layer rather than rubber.